WOMEN FACTORY WORKERS AND HOUSING CHOICE Case study: The experience of women factory workers in SIER Surabaya - Arifin, Lilianny Sigit (DIMENSI (Journal of Architecture and Built Environment), 2004)
This paper give the contribution to the characteristic of women factory workers in housing choice. The phenomena about women factory workers have low affordability in housing, was explored again by life story research approach. With qualitative methods, it was found that the cheap price is not the key factors that influincing them in housing choice. But their characteristic as young workers, migrant workers, and women workers showed the essential factors in housing choice.